Analyzing the Impact of a SEZ on Rural Livelihood: Understanding the Impact of SEZs on Rural Livelihood in Tamil Nadu (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The development process underway in India has significantly altered the occupational pattern of the people. From being an agrarian society, the history of development planning in India has facilitated an occupational shift of labourers from primary to secondary and tertiary sectors. The nature and economic implications of such occupational shifts depends upon access to productive resources, access to education, patterns of urbanisation ad industrialisation in respective regions. Proliferation of industrial estates, special economic zones (SEZ) and export processing zones in the recent years have catalysed a drastic change in the livelihood options available for the people. Tamil Nadu, being the second most urbanized state with a wide range of industrial clusters, has witnessed different patterns of occupational shifts across the state. The data from a complete census enumeration of households in Oragadam industrial estate near Chennai revealed a sudden occupational shift from primary to manufacturing sectors together with dispossession of productive assets. This paper attempts to map the changing livelihood strategies of the local people owing to the inception of the SEZ.